Ever-current issues in our school: A review on violence and inclusion (Research, Society and Development, 2022)
The study aims to promote a reflection on the relationship between social inclusion and violence in the school environment from the reality of some Brazilian public schools permeated by an unequal educational system and to present a municipal public school with a model school structure for all. It is a research of a qualitative nature, of the literature review type. The searches were carried out from a bibliographic survey in three digital databases – CAPES; Scielo and Google Scholar, as well as books, within the period from June to August 2022. In a context of social inequality, the result of the economic crises that plague our country and affect with greater impact the most vulnerable groups, schools, especially the public ones, feel the effects of this imbalance. This scenario has been provoking a context of exclusion in the school space that triggers countless forms of violence, hindering the process of social inclusion and a school for all. We use a model public school to show a well-planned school with efficient management is able to promote the inclusion of students and the reduction of the different expressions of violence. In conclusion, we understand that education is an important tool in the fight against social inequalities, especially when it offers more equal and fair conditions for the most diverse students to enjoy a quality education capable of contributing to the reversal of the current situation, minimizing violence and promoting inclusion.